2021
DOI: 10.1007/s12190-021-01497-x
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics of a higher order difference equation with a quadratic term

Abstract: In this paper, we investigate the dynamics of following higher order di¤erence equation x n+1 = A + B x n x 2 n m with A; B and initial conditions are positive numbers, and m 2 f2; 3; g. Especially we study the boundedness, periodicity, semi-cycles, global asymptotically stability and rate of convergence of solutions of related higher order di¤erence equations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Finally, they showed that the positive solutions of System (3) are boundedness and persistence, and that the unique positive equilibrium point of System (2) is globally asymptotically stable. Other related difference equations and systems of difference equations can be found in references [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they showed that the positive solutions of System (3) are boundedness and persistence, and that the unique positive equilibrium point of System (2) is globally asymptotically stable. Other related difference equations and systems of difference equations can be found in references [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been a rapid increase in studying the theory and applications of difference equations, for related studies, see [3,4,5,19,20]. Especially, the studies that concern the relation between the special sequences and the closed form of the solutions of difference equations or systems have been received great interest by many researchers for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…In [11], Taşdemir studied the periodicity, boundedness, semi-cycles, global asymptotically stability and rate of convergence of solutions of the following higher order difference equation…”
Section: Introductionmentioning
confidence: 99%